Analisis Return On Investment dan Return On Advertising Spend Client Perusahaan Nexcommerce (Studi Kasus Pada Brand Pakaian Tahun 2024) - Mohamad Arie Apriyadi; Neng Tika Septika S (Lembaga Pengembangan Kinerja Dosen, 2025)
The industrial revolution has advanced into the Society 5.0 era, where digital platforms dominate shopping activities, requiring businesses to adapt their marketing strategies. However, many lack understanding among business actors in managing advertising strategies via platforms leads to wasteful advertising costs. Digital marketing services such as those provided by Nexcommerce can help manage and evaluate the effectiveness of advertising investments on each platform using profitability ratios, Return On Investment and Return On Advertising Spend. The objective of this research is to analyze Return On Investment in measuring the effectiveness of financial performance in the allocation of marketing campaign investment costs and Return On Advertising Spend in measuring the effectiveness of financial performance in the allocation of advertising costs on the Shopee and TikTok platforms on 2024 for Nexcommerce's client, a clothing brand. This research uses a qualitative approach with a case study research design, utilizing primary and secondary data sources through observation, interviews, and documentation. The results show that the clothing brand's Return On Investment in 2024 had an average value of 573.22% (effective), while Return On Advertising Spend on the Shopee platform yielded an average of 8.0 (effective), and on the TikTok platform, an average of 10.1 (highly effective).